1999
DOI: 10.1093/jac/43.2.261
|View full text |Cite
|
Sign up to set email alerts
|

The control of hyperendemic glycopeptide-resistant Enterococcus spp. on a haematology unit by changing antibiotic usage

Abstract: The rectal carriage of glycopeptide-resistant Enterococcus spp. (GRE) had been established at approximately 50% in a series of prevalence studies on a busy haematological malignancy unit. The aim of this study was to reduce the chance of patients acquiring GRE. A prospective three-phase sequential study was performed. In Phase 1, the acquisition rate of GRE detectable by rectal swab was measured without any intervention for a period of 4 months. For the following 8 months (Phase 2), the first-line treatment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(101 citation statements)
references
References 16 publications
3
97
0
1
Order By: Relevance
“…21 Whether there is a cause-effect between cycling and VRE emergence is less clear. 22 On one hand, the use of anaerobic coverage (pip-tazo) has been associated with increased incidence of VRE colonization after its use, during the period of recovery of the original gut microflora. [23][24][25] On the other hand, a previous study by Bradley et al 22 found a decreased incidence of VRE while cycling ceftazidime and pip-tazo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Whether there is a cause-effect between cycling and VRE emergence is less clear. 22 On one hand, the use of anaerobic coverage (pip-tazo) has been associated with increased incidence of VRE colonization after its use, during the period of recovery of the original gut microflora. [23][24][25] On the other hand, a previous study by Bradley et al 22 found a decreased incidence of VRE while cycling ceftazidime and pip-tazo.…”
Section: Discussionmentioning
confidence: 99%
“…22 On one hand, the use of anaerobic coverage (pip-tazo) has been associated with increased incidence of VRE colonization after its use, during the period of recovery of the original gut microflora. [23][24][25] On the other hand, a previous study by Bradley et al 22 found a decreased incidence of VRE while cycling ceftazidime and pip-tazo. A sample of VRE isolates collected from our hematologyoncology unit during our study period was found to be primarily clonal by pulsed-field gel electrophoresis analysis (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…33 Although introduced as part of the overall strategy, the reduction in use did not occur until the outbreak was almost completely controlled. It is possible that continuing restrictions may help maintain control, but its role in the eradication process is uncertain.…”
Section: May 2004mentioning
confidence: 99%
“…There are a large number of studies showing the impact of antibiotic use on the prevalence of VRE [19][20][21][22] . The majority of these reports show the previous use of antibiotics, e.g., vancomycin, carbapenem, metronidazole, clindamycin, and cephalosporin, as independent risk factor for the acquisition of VRE.…”
Section: Resultsmentioning
confidence: 99%